2021
DOI: 10.3389/fmed.2021.666949
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Hyponatremia for Predicting Poor Outcome in Patients With COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background: This meta-analysis aimed to assess the prognostic value of hyponatremia in patients with COVID-19.Methods: We performed a systematic literature search on PubMed, Scopus, ScienceDirect, and Wiley up until January 26, 2021. The key exposure was hyponatremia, defined as sodium level below the reference level. The outcome of interest was poor outcome, which was a composite of mortality, severe COVID-19, and prolonged hospitalization. Severe COVID-19 was defined severe CAP or needing ICU care or IMV. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 31 publications
5
26
2
Order By: Relevance
“…At admission, 26.5% patients had hyponatremia: this finding is consistent with data from a meta-analysis on 11,493 COVID-19 patients showing a 24% pooled incidence for this disorder ( 27 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At admission, 26.5% patients had hyponatremia: this finding is consistent with data from a meta-analysis on 11,493 COVID-19 patients showing a 24% pooled incidence for this disorder ( 27 ).…”
Section: Discussionsupporting
confidence: 87%
“…The first, retrospective Chinese data on hyponatremia in COVID-19 pneumonia reported a 10–27% prevalence, which is far lower than the 60% previously demonstrated for SARS-CoV-1 ( 24 , 25 , 26 ). Data from a recent meta-analysis on the same topic showed a pooled incidence of 16–31% for hyponatremia ( 27 ), which has been directly correlated with PaO 2 /FiO 2 ratio, inversely with IL-6 and associated with worse COVID-19 outcomes (non-invasive ventilation, ICU transfer, death) ( 24 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ). Despite its prognostic value in critical illnesses, data concerning COVID-19-related hypernatremia are scarce ( 24 , 33 , 34 , 35 ); specifically, only one study looked for the development of hypernatremia in COVID-19 inpatients, showing this was associated with in-hospital mortality ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypovolemic hyponatremia is common in COVID 19 infected patients after admission because of the presence of increased insensible loses (taquipnea, fever), vomiting, diarrhea, and anorexia that accompany severe respiratory symptoms and the use of hypotonic fluids ( 11 ). However, in our population hyponatremia was present at admission before any therapeutic intervention took place.…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatremia can result from inflammation due to non-osmotic stimuli for vasopressin production (9) and is a risk factor for death in general hospitalized patients (10). Thus, hyponatremia linked to severe inflammation could be another prognostic factor for poor outcomes in COVID 19 infected patients as has been recently shown in a recent meta-analysis (11). However, all the previous studies have been retrospective or cross-sectional in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Since IL-6 is able to induce vasopressin secretion by a direct hypothalamic stimulation and by inducing alveolar basement membrane injury and pulmonary hypoxia and vasoconstriction [ 44 , 45 , 46 , 47 ], the pro-inflammatory cytokine may represent the common denominator of both acute respiratory insufficiency and syndrome of inappropriate antidiuresis (SIAD)-related hyponatremia. A very recent metanalysis of 8 studies and 11,493 patients showed a correlation of hyponatremia with COVID-19 poor outcomes (a composite of mortality, prolonged hospitalization and severe COVID-19, defined as severe pneumonia and/or needing intensive care unit support/invasive mechanical ventilation; OR 2.65 [1.89, 3.72], p < 0.001; I2: 67.2%, p = 0.003), with a 37% sensitivity and 82% specificity; while normal serum [Na + ] is associated with a 16% post-test probability of a worse prognosis, the presence of hyponatremia increases this probability up to 33% [ 48 ].…”
Section: Hyponatremia and Healthmentioning
confidence: 99%